Simultaneous Determination of the Absolute Configuration of Twelve Monosaccharide Enantiomers from Natural Products in a Single Injection by a UPLC-UV/MS Method - Wang, Yan-Hong; Avula, Bharathi; Fu, Xiang; Wang, Mei; Khan, Ikhlas A. (Planta Medica, 2012)
In natural product chemistry, it is often crucial to determine sugar composition as well as the absolute configuration of each monosaccharide in glycosides. An ultra-performance liquid chromatography method using both photodiode array (PDA) and mass spectrometry detectors (UPLC-UV/MS) was developed for qualitative analysis of the absolute configuration of monosaccharide enantiomers. Within a single injection, 16 monosaccharide derivatives including 6 pairs of aldose enantiomers (D/L-glucose, D/L-galactose, D/L-allose, D/L-arabinose, D/L-xylose, and D/L-fucose) and 4 other monosaccharides (L-rhamnose, 2-deoxy-D-glucose, 6-deoxy-D-glucose, and 2-deoxy-D-glalactose) were identified in less than 25 minutes. It was found that the structures of derivatives of sugar enantiomers correlated with retention time. Among derivatives of sugar enantiomers in the current study, the stereoisomer of R-configuration at C-3′ retained longer than the corresponding S-configuration isomer. The UPLC-MS method can increase sensitivity of detection of the saccharides by more than 10 times compared to previously reported methods. The one-pot reaction of monosaccharide with L-cysteine methyl ester and phenyl isothiocyanate is easily reproduced, clean, and relatively simple in a screw-capped reaction vial. The developed method was successfully applied for the analysis of different types of glycosides, viz., glycosides of triterpenes, steroids, and flavonoids, that commonly exist in nature. The absolute configurations of composed monosaccharides are clearly characterized from tested samples.
Keywords: monosaccharide; enantiomer; arylthiocarbamate derivatives; absolute configuration; glycosides; UPLC-UV/MS